Calf/female ratio and population dynamics of wild forest reindeer in relation to wolf and moose abundances in a managed European ecosystem - Kojola, Ilpo; Hallikainen, Ville; Heikkinen, Samuli; Forsman, Jukka T.; Kukko, Tuomas; Pusenius, Jyrki; Antti, Paasivaara (Public Library of Science, 2021)
The alternative prey hypothesis describes the mechanism for apparent competition whereby the mortality of the secondary prey species increases (and population size decreases decreases) by the increased predation by the shared predator if the population size of the primary prey decreases. Apparent competition is a process where the abundance of two co-existing prey species are negatively associated because they share a mutual predator, which negatively affects the abundance of both prey Here, we examined whether alternative prey and/or apparent competition hypothesis can explain the population dynamics and reproductive output of the secondary prey, wild forest reindeer (Rangifer tarandus fennicus) in Finland, in a predator-prey community in which moose (Alces alces) is the primary prey and the wolf (Canis lupus) is the generalist predator.
Keywords: Rangifer tarandus fennicus; Alces alces; Canis lupus; Predator-prey dynamics